Conservation and Development of Community-Based Agro-Ecotourism in Barangay Digkila-an, Iligan City - Sison, Maria Pia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2022)
This paper assessed the agro-ecotourism potentials and prospects of Barangay Digkilaan by examining some of its environmental elements, agro-elements, market viability and community people’s skills, capability, and social acceptability of the local community on their cooperation for income generating activities for agro-ecotourism and environmental protection. Environmental elements include physical landscape, existence of natural resources such as waterfalls, agroforestry and indigenous farm products were also identified. Farm to market road, potential market of agro-ecotourism products and services were determined. Skills and capability of community residents were also assessed for the prospect of potential income generating activities for agro-ecotourism development of Barangay Digkilaan. Participatory Resource Appraisal was done in gathering necessary data. Transect walk was conducted as a technique in identifying the environmental elements and market viability of the research area. Also, Focus Group Discussion (FGD) with the Barangay officials and local residents were conducted to gather information about the proposed agro-ecotourism project as well as current issues. A total of 82 participants participated in the FGD. Results revealed that Barangay Digkilaan has a considerable degree of potential for agro-ecotourism development. Collaborative policy-making in enhancing community-based agro-ecotourism is also highlighted in this study to achieve sustainability: environmental sustainability, social sustainability and economic sustainability.